A dendritic cell-targeted chimeric hepatitis B virus immunotherapeutic vaccine induces both cellular and humoral immune responses in vivo - Rajan George; Allan Ma; Bruce Motyka; Yuenian Eric Shi; Qiang Liu; Philip Griebel (Taylor & Francis Group, 2020)
Chimigen® HBV Immunotherapeutic Vaccine (C-HBV), a recombinant chimeric fusion protein comprising hepatitis B virus (HBV) S1 and S2 surface antigen fragments, Core antigen and a murine monoclonal antibody heavy chain fragment (Fc), was designed and produced in Sf9 insect cells. C-HBV targets the host immune system through specific receptors present on dendritic cells (DCs) which facilitates antigen internalization, processing, and presentation on MHC class I and II to induce both cellular and humoral immune responses against HBV antigens. T cell responses, previously assessed by ex vivo antigen presentation assays using human peripheral blood mononuclear cell (PBMC)-derived DCs and T cells from uninfected and HBV chronic-infected donors, demonstrated that C-HBV was highly immunogenic. A vaccine dose response study was performed in sheep to analyze the immunogenicity of C-HBV in vivo. Sheep (n = 8/group) received three consecutive subcutaneous injections of each dose of C-HBV at four-week intervals. Analysis of serum antibody levels confirmed C-HBV induced a dose-dependent antibody response to C-HBV and S1/S2-Core. Kinetics of the S1/S2-Core specific antibody response was similar to hepatitis B surface antigen (HBsAg)-specific antibody responses induced by ENGERIX-B. Analysis of cell-mediated immune responses (CMI) confirmed C-HBV induced both dose-dependent S1/S2-Core-specific lymphocyte proliferative responses and IFN-γ secretion. These responses were stronger with blood lymphocytes than with cells isolated from the lymph node draining the vaccination site. No correlation was seen between antibody titers and CMI. The results confirm C-HBV is an effective delivery vehicle for the induction of T cell responses and may be an appropriate candidate for immunotherapy for chronic HBV infections.